Historical psychology: the versions of synthesis - Bagdonas, Albinas (Lietuvos istorijos studijos, 1997)
Different aspects and problems of historical psychology in the paper are discussed. Historical psychology as an interdisciplinary area of knowledge is complicated by different historical methodologies and experimental psychology (individualized approach vs. generalized approach according to H. Rickett’s dichotomy). The introduction of the principle of historicism (historical determinism) into psychology resulted in the formation of Piagetian genetic psychology, Vygotsky’s cultural psychology, and the French school of historical psychology. Another source of development of the last one was the investigations of "psychology of nations" (W. Wundt). The most developed version of the synthesis of psychology and history is psychohistory, based on the psychoanalytical tradition (E. Erikson). Four fruitful points of interaction of psychology and history are discussed: 1) the history of psychology as science; 2) historical (sociocultural) determinism; 3) the analysis of psychological variables as factors of human history and progress; 4) the content of historical psychology (evolution and history of psychological functions, psychological recapitulation, reconstruction of historical personalities, and psychological variables of the groups, etc.).